2017
DOI: 10.1186/s41241-017-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antitumor potential of extracts from different parts of Bauhinia variegata linn. Against b16f10 melanoma tumour model in c57bl/6 mice

Abstract: Background: Melanoma is a metastatic type of skin cancer that is difficult to treat and the majority of efforts are directed to the design of new drugs. Medicinal Plants have been the primary source of medicines since life on earth; more than 50% of existing cancer treatments is derived from plants. Bauhinia variegata is well-known medicinal plant used from the ancient era to till date for their medicinal values. Scientific literatures have not documented any evidence of the antitumour potential of Bauhinia va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 86 publications
0
12
0
1
Order By: Relevance
“…Predições farmacocinéticas das substâncias isoladas de Bauhinia variegata. Pandey, 2017;Mishra, et al, 2013;Rajkapoor, et al, 2003). A análise desse processo é importante tendo em vista que a morte celular programada corresponder a um mecanismo bioquímico que subsidia o controle de células nos organismos multicelulares, promovendo a homeostase dos tecidos e sendo extremamente vital para células infectadas, mutadas ou danificadas (Kruidering & Evan, 2000).…”
Section: Resultsunclassified
“…Predições farmacocinéticas das substâncias isoladas de Bauhinia variegata. Pandey, 2017;Mishra, et al, 2013;Rajkapoor, et al, 2003). A análise desse processo é importante tendo em vista que a morte celular programada corresponder a um mecanismo bioquímico que subsidia o controle de células nos organismos multicelulares, promovendo a homeostase dos tecidos e sendo extremamente vital para células infectadas, mutadas ou danificadas (Kruidering & Evan, 2000).…”
Section: Resultsunclassified
“…It was observed that hydromethanolic extracts of leaf, stem bark and flower of Bauhinia variegata,at the dose of 500 and 750 mg / kg of body weight, significantly reduced melanoma tumor volume. [19] This effect may be attributed to the presence of polar phytoconstituents such as alkaloids, flavonoids, tannins, terpenoids, and glycosides present in the crude extract of B. variegata. [19] Camargo et al studied the antitumor potential with extract of Zingiber officinale showed a cytotoxic effect for human kidney tumor cell with no harm effect for the normal cells.…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…[19] This effect may be attributed to the presence of polar phytoconstituents such as alkaloids, flavonoids, tannins, terpenoids, and glycosides present in the crude extract of B. variegata. [19] Camargo et al studied the antitumor potential with extract of Zingiber officinale showed a cytotoxic effect for human kidney tumor cell with no harm effect for the normal cells. This effect may be due to the bioactive compounds of Z. Officinale phenolics compounds, total flavonoids, yellow flavonoids and anthocyanins.…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…All of these justify the urgency in the search for naturally occurring anticancer drugs with fewer side effects and designed to overcome the resistance problem. Several studies have already been carried out with plant extracts in relation to melanoma cell line B16-F10; for example, Pandey [ 23 ], showed the in vivo antitumor potential of extracts from the different parts of Bauhinia variegata Linn. Rajasekar et al [ 24 ] showed the anticancerous effect of Lithospermum erythrorhizon extract in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%